2022
DOI: 10.1007/s00146-022-01450-x
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in local governments: perceptions of city managers on prospects, constraints and choices

Abstract: Highly sophisticated capabilities of artificial intelligence (AI) have skyrocketed its popularity across many industry sectors globally. The public sector is one of these. Many cities around the world are trying to position themselves as leaders of urban innovation through the development and deployment of AI systems. Likewise, increasing numbers of local government agencies are attempting to utilise AI technologies in their operations to deliver policy and generate efficiencies in highly uncertain and complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…Fifth, the public sees value in what AI currently offers and potentially could bring in urban services and disaster management. Recently conducted studies, by Nili et al ( 2022 ), Sanchez et al ( 2022 ) and Yigitcanlar et al ( 2022b ), revealed insights into public sector experiences about deploying AI and offer a wide spectrum of AI adoption prospects for local governments as creating efficiencies, tackling complexity, managing repetitive tasks, processes, and decisions, automating routine decisions, minimising errors, and improving productivity that particularly benefit customer services, cybersecurity, policy and decision-making, environmental and development control, service and infrastructure management, urban planning, and performance review.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the public sees value in what AI currently offers and potentially could bring in urban services and disaster management. Recently conducted studies, by Nili et al ( 2022 ), Sanchez et al ( 2022 ) and Yigitcanlar et al ( 2022b ), revealed insights into public sector experiences about deploying AI and offer a wide spectrum of AI adoption prospects for local governments as creating efficiencies, tackling complexity, managing repetitive tasks, processes, and decisions, automating routine decisions, minimising errors, and improving productivity that particularly benefit customer services, cybersecurity, policy and decision-making, environmental and development control, service and infrastructure management, urban planning, and performance review.…”
Section: Discussionmentioning
confidence: 99%
“…An overlapping but distinct area of research focuses on the role of AI in the built environment, so-called urban AI [1,42,56,57,67,73,79]. Many application contexts here are mobility-related, for example smart electric vehicle charging [1]; autonomous vehicles [56]; and automated parking control systems [67].…”
Section: Public and Urban Aimentioning
confidence: 99%
“…AI is one of the most disruptive technologies of our time with many powerful applications that cities around the globe have started to take advantage of [17]. According to Yigitcanlar et al [18], "in the context of cities, AI is the engine of automated algorithmic decisions that generate various efficiencies in the complex and complicated local government services and operations. Managing city assets with structural health monitoring, energy infrastructure fault detection and diagnosis, accessible customer service with chatbots, and automated transportation with autonomous shuttle busses are among the many examples of how AI is being utilized in the local government context."…”
Section: -Literature Background: Societal Issues and Ai In Urban Serv...mentioning
confidence: 99%
“…The presented complex mix of SCs is the foundation of the empirical section detailing the current socioeconomic structuring of AI perceptions (see Section 4). While there are some studies on what urban managers think on the prospects and constraints of AI in the context of local government services [18], there is a knowledge gap in understanding what the public thinks about AI adoption in urban services-especially considering the societal differentiation and digital divides. This study focuses on the socioeconomic variables (see Table 2) and locations (Australia and Hong Kong) to bridge this gap.…”
Section: -5-sustainability Wellbeing and Health (Sc5)mentioning
confidence: 99%